Menggugah peran hukum humaniter internasional Islam dalam mengurai konflik etnis perspektif sejarah - Rosyid, Moh (IJTIHAD Jurnal Wacana Hukum Islam dan Kemanusiaan, 2012)
The defamation of minority ethnics and groups by the authority and the majority has been exposed by the media throughout history. This condition is contrary to the Islamic concept of rahmatan lilâalamin. The concept will not be materialized if the expert of humanitarian law does not involve in the formulation of Islamic humanitarian law. This topic is proposed by the author to persuade the expert of Islamic law to be more active in exploring the concept of prosperous life according to Islam. The author does not explore the topic from legal point of view but rather from historical point of view that crime and genocide has colored global life. If this condition is not addressed immediately and appropriately, we should concern that misguidance will be always characterized our life. Persuading humanitarian law expert is a scientist contribution to create a prosperous life and prevent a conflict. International humanitarian law is a part of international law consisting of diplomatic law, maritime law, law of international treaty, and space law. Due to its significance, it necessitates Islam to coloring humanitarian law. Islam may contribute to humanitarian law through the expert of Islamic law. Islam may be used as a frame of humanitarian law because it establishes a world full of compassion without any form of discrimination.